Contamination of some Residues in Pacific White Shrimp (Litopenaeus vannamei Boone, 1931) in Shrimp Pond from Chanthaburi and Trat Provinces - สมนึก ชวัลรัตน์; โพธิพัฒน์ จักรพันธ์; เมฆประยูร ศุทธินี (KKU Science Journal, 2015)
Four types of residue including organophosphate insecticides, heavy metals (lead, copper, cadmium and zinc), pathogenic bacteria (Vibrio cholerae, Vibrio vulnificus and Vibrio parahaemolyticus) and antibiotics (Oxytetracycline, Tetracycline and Nitrofuran) in Pacific white shrimp from shrimp pond in four Districts (Muang, Laem Sing, Kloong and Tha Mai Districts) of Chanthaburi Province, and three Districts (Muang, Laem Ngob and Klong Yai Districts) of Trat Province were determined. Results show that only copper level exceeds standard value specified by Ministry of Public Health from Kloong District, Chanthaburi Province (32.18±8.64 µg/g). The result also indicates residue of antibiotics, especially tetracycline at a quantity of less than 0.05 µg/kg in area of Muang District, Chanthaburi Province, V. parahaemolyticus at 3.0±2.4 MPN/g in 25 g of sample from Laem Ngob District, Trat Province and zinc at 17.30±4.67 µg/g from Klong Yai Districts, Trat Province. However, it was less than specified standard value. In addition, no residue of organophosphate insecticides, V. cholerae, V. vulnificus, oxytetracycline and nitrofuran was detected in all samples from both Chanthaburi and Trat Provinces.